2017
DOI: 10.1155/2017/1564634
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cellular Effects Directly Induced by Magnetic Nanoparticles under Magnetic Fields

Abstract: The interaction of magnetic nanoparticles (MNPs) with various magnetic fields could directly induce cellular effects. Many scattered investigations have got involved in these cellular effects, analyzed their relative mechanisms, and extended their biomedical uses in magnetic hyperthermia and cell regulation. This review reports these cellular effects and their important applications in biomedical area. More importantly, we highlight the underlying mechanisms behind these direct cellular effects in the review f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 124 publications
(159 reference statements)
0
28
0
Order By: Relevance
“…In the case of MNPs internalized by cells, the chances to get in contact with cell organelles are increased, resulting in a high efficiency of the MHT treatment even when low MNPs concentrations are used. In this respect, Chen et al 31 included in their excellent review several reports about targeted magnetic hyperthermia showing that if MNPs are combined with or incorporate into tumor cells, a high impact on the cellular viability without a perceptible macroscopic temperature rise can be achieved. Also, Marcos-Campos et al showed that the selective cytotoxicity of MNPs under an AMF could be the result of the local damage produced by MNPs.…”
Section: Mechanisms For Different Wht and Mht Cytotoxic Effectsmentioning
confidence: 99%
“…In the case of MNPs internalized by cells, the chances to get in contact with cell organelles are increased, resulting in a high efficiency of the MHT treatment even when low MNPs concentrations are used. In this respect, Chen et al 31 included in their excellent review several reports about targeted magnetic hyperthermia showing that if MNPs are combined with or incorporate into tumor cells, a high impact on the cellular viability without a perceptible macroscopic temperature rise can be achieved. Also, Marcos-Campos et al showed that the selective cytotoxicity of MNPs under an AMF could be the result of the local damage produced by MNPs.…”
Section: Mechanisms For Different Wht and Mht Cytotoxic Effectsmentioning
confidence: 99%
“…Importantly, this has implications for IONP design and whether efforts to improve the internalisation of these nanoparticles through functionalisation with targeting agents are necessary. Nonetheless, further studies are needed to elucidate whether intracellular nanoparticles can contribute to treatment efficacy in alternative ways such as instigating anti-tumour immune responses or disrupting intracellular signalling pathways that may enhance the effects of combination therapies, as magnetic hyperthermia has been reported to do [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species are resulted to make the apoptosis of osteoclast. 28 With a reduction of osteoclast cell number, this nanoparticle gives authority to osteocytes to make new bone tissue. This makes the magnetic nanoparticle has a therapeutic role.…”
Section: Magnetic Nanoparticle As Osteoporosis Therapymentioning
confidence: 99%